Postoperative complications and mobilisation following major abdominal surgery with vs. without fitness tracker-based feedback (EXPELLIARMUS): study protocol for a student-led multicentre randomised controlled trial (CHIR-Net SIGMA study group) - Schwab, Marius; Brindl, Niall; Studier-Fischer, Alexander; Tu, Thomas; Gsenger, Julia; Pilgrim, Max; Friedrich, Mirco; Frey, Pia-Elena; Achilles, Christina; Leuck, Alexander; Bürgel, Thore; Feißt, Manuel; et al. (Trials, 2020)
Postoperative complications following major abdominal surgery are frequent despite progress in surgical technique and perioperative care. Early and enhanced postoperative mobilisation has been advocated to reduce postoperative complications, but it is still unknown whether it can independently improve outcomes after major surgery. Fitness trackers (FTs) are a promising tool to improve postoperative mobilisation, but their effect on postoperative complications and recovery has not been investigated in clinical trials.
Gesehen am 20.04.2020